2018
DOI: 10.1111/jomf.12471
|View full text |Cite
|
Sign up to set email alerts
|

Do the Health Benefits of Marriage Depend on the Likelihood of Marriage?

Abstract: Marriage promotion initiatives presume substantial health benefits of marriage. Current literature, however, has provided inconsistent results on whether these benefits would be shared by people unlikely to marry. We investigate whether the physical and mental health benefits of marriage depend on the likelihood of marriage. Whereas prior studies have compared health benefits of marriage across a single predictor of marriage chances, we define the likelihood of marriage as a composite of demographic, economic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 74 publications
(107 reference statements)
3
17
0
Order By: Relevance
“…For example, researchers increasingly use matching techniques, which reduce imbalance, model dependence, and the influence of confounding variables and provide insight into long‐assumed causal family‐health linkages. Tumin and Zheng () used a composite of demographic, economic, and health characteristics to generate propensity scores for estimating the likelihood of marriage and found that once these propensities for marriage were taken into account, married adults were only modestly healthier than unmarried adults both physically and mentally. Other techniques to address causal inference, such as fixed effect models, placebo regressions, and inverse‐probability‐weighted estimation of marginal structural models, are also gaining popularity in family and health studies (Gangl, ).…”
Section: Advances In Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, researchers increasingly use matching techniques, which reduce imbalance, model dependence, and the influence of confounding variables and provide insight into long‐assumed causal family‐health linkages. Tumin and Zheng () used a composite of demographic, economic, and health characteristics to generate propensity scores for estimating the likelihood of marriage and found that once these propensities for marriage were taken into account, married adults were only modestly healthier than unmarried adults both physically and mentally. Other techniques to address causal inference, such as fixed effect models, placebo regressions, and inverse‐probability‐weighted estimation of marginal structural models, are also gaining popularity in family and health studies (Gangl, ).…”
Section: Advances In Data and Methodsmentioning
confidence: 99%
“…There are two primary explanations for these patterns. First, through selection, people who are healthier and wealthier are more likely to marry and remain married, making it appear that marriage benefits health when it is actually health that predicts marriage (Tumin & Zheng, ). Second, the married enjoy certain resources that promote health, including pooled economic assets, greater access to emotional and social support, and the spouse's encouragement and coercion of healthy behaviors (i.e., social control; Rendall et al, ).…”
Section: Family Ties and Adult Healthmentioning
confidence: 99%
“…The married experience a mental health advantage relative to the unmarried, including lower levels of depression and anxiety (Mernitz and Dush 2016; Van Hedel et al 2018). This is in part because spouses provide emotional support to each other during times of stress (Holt-Lunstad, Birmingham, and Jones 2008), marriage provides access to health insurance and other resources that promote access to affordable mental health care (Walker et al 2015), and those who are mentally healthier are more likely to get and stayed married (Tumin and Zheng 2018). Although emotional support, financial resources, and selection processes are key to the marital mental health advantage, we do not know whether and, if so, how spouses encourage or pressure one another to seek professional mental health care.…”
mentioning
confidence: 99%
“…In fact, having both appears to magnify firefighter QWL given that both forms of relational quality emerged as significant predictors of QWL, and the positive effect of one form of relational quality is enhanced to some degree in the presence of the other. Researchers have already demonstrated that marital quality is associated with a host of positive physical and mental health outcomes for men (Tumin & Zheng, 2018; Wanic & Kulic, 2011), including lower rates of depression and lower alcohol consumption (Haddock et al, 2016). One meaningful implication of our results, then, is that they extend marriage benefit research into the fire service context and provide further support for the contention that marital quality, when examined by itself, is positively associated with firefighters’ job satisfaction and QWL (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of marriage may be particularly important to firefighters given that high-quality marriages benefit men more so than women (Wanic & Kulik, 2011), particularly for men who stay married over the course of their lives (Tumin & Zheng, 2018). In earlier research, for example, married men reported better overall health compared to single or never-married men, with unmarried men facing a 250% greater risk for mortality than married men (Ross, Birmingham, & Jones, 1990).…”
Section: Literature Reviewmentioning
confidence: 99%